[latex] \frac{42}{7а- а^{2} } - \frac{6}{а} при а=2[/latex]

[latex] \frac{42}{7а- а^{2} } - \frac{6}{а} при а=2[/latex]
Гость
Ответ(ы) на вопрос:
Гость
[latex]\frac{42}{7a- a^{2} } - \frac{6}{a} =\frac{42}{a\cdot (7- a) } - \frac{6}{a} =\frac{42}{a\cdot (7- a) } - \frac{6(7-a)}{a(7-a)} =\frac{42-6(7-a)}{a(7-a)} = \\ \\ =\frac{42-42+6a}{a(7-a)} =\frac{6a}{a(7-a)} =\frac{6}{7-a} [/latex] при а=2 получаем [latex] \frac{6}{7-2}= \frac{6}{5}=1,2 [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы